2013
DOI: 10.1002/mus.23689
|View full text |Cite
|
Sign up to set email alerts
|

Growth‐associated protein‐43 expression in cocultures of dorsal root ganglion neurons and skeletal muscle cells with different neurotrophins

Abstract: These results offer new clues for a better understanding of the effects of distinct NTs on GAP-43 expression in DRG sensory neurons in the presence of target SKM cells and implicate NTs and target SKM cells in DRG neuronal regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Many experimental results showed that the secretion of neurotrophic factors is reduced after peripheral nerve injury, and an exogenous neurotrophic factor 3 (neurotrophin 3, NT-3) promotes nerve regeneration and protects against muscle atrophy [9,10]. However, the mechanism of such effects remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Many experimental results showed that the secretion of neurotrophic factors is reduced after peripheral nerve injury, and an exogenous neurotrophic factor 3 (neurotrophin 3, NT-3) promotes nerve regeneration and protects against muscle atrophy [9,10]. However, the mechanism of such effects remains unclear.…”
Section: Introductionmentioning
confidence: 99%